(untitled) (Journal of Philosophy Culture and Political Science, 2018)
This article examines the philosophy of Ebelek (Ebelek is symbol of weak plants which do not have deep roots, as result turn into a rolling field, a fluff knowing ..... ). The philosophy of Marxism-Leninism is experiencing today, the status of Ebelek. The Marxism-Leninism philosophy starts with the philosophy of G. F. Hegel. «The philosophy of Ebelek» historically existed in the spiritual culture of mankind and can exist today. A person comes to the truth through the delusion. The philosophy of Ebelek is an echo of delusion. The world of today, society needs a different philosophy. The core of a new philosophy type is humanism. The author concludes that the philosopher neglecting humanism stands in the way of philosophy of Ebelek. How sudden wind appear and the different schools disappear, so maybe in the future. Key words: philosophy of Ebelek, the dialectic, mystification, Kazakh philosophy, Hegel’s philosophy, pluralism, communism, logomachia pacifism.